Cardiovascular disease in thymic cancer patients - Khemka, Abhishek; Clasen, Suparna C.; Loehrer, Patrick J.; Roberts, Anna R.; Golzarri-Arroyo, Lilian; Badve, Sunil S.; Raman, Subha V.; Hui, Siu L.; Schleyer, Titus K. L. (Frontiers in Cardiovascular Medicine, 2024)
Cancer patients may have increased risk for adverse cardiac events, but our understanding of cardiovascular risk in thymic cancer patients is not clear. We sought to characterize baseline cardiometabolic risk factors before thymic cancer diagnosis and the potential association between cancer treatment and subsequent cardiac events.This was a retrospective cohort study evaluating patients with thymic cancer from 2003 to 2020 compared to age-and sex-matched controls without cancer. Baseline cardiovascular risk factors, cancer characteristics, and incidence of cardiac events were collected from the health information exchange. Multivariable regression was used to examine the impact of cardiovascular risk factors and cancer therapies.We compared 296 patients with pathology-confirmed thymic cancer to 2,960 noncancer controls. Prior to cancer diagnosis, thymic cancer patients (TCPs) had lower prevalence of hypertension, dyslipidemia, and diabetes mellitus and similar rates of obesity, tobacco use, and pre-existing cardiovascular disease (CVD) compared to controls. After diagnosis, high-risk TCPs (>2 cardiovascular risk factors or pre-existing CVD) had higher risk for cardiac events (HR 3.73, 95% CI 2.88-4.83, p<0.001). In the first 3 years after diagnosis, TCPs had higher incidence of cardiac events (HR 1.38, 95% CI 1.01-1.87, p=0.042). High-risk TCPs who received radiotherapy or chemotherapy had higher risk of cardiac events (HR 4.99, 95% CI 2.30-10.81, p<0.001; HR 6.24, 95% CI 2.84-13.72, p<0.001).Compared to noncancer controls, TCPs experienced more cardiac events when adjusted for risk factors. Patients with multiple cardiovascular risk factors receiving radiotherapy or chemotherapy had higher incidence of cardiac events.